Hispanic and Non-Hispanic Adult Learners: Analytical Thinking and Affiliation - Catherine A Cherrstrom (Adult Education Research Conference, 2023)
This study examined 364 Hispanic and non-Hispanic adult learners using linguistic inquiry and word count (LIWC) of reflective writing assignments with implications for adult learners and educators.
Keywords: adult learners; nontraditional students; Hispanic students; linguistic analysis and word count